Coaching Collaboration: Training Strategy for Improving the Quality of Scientific Writing - Naily Kamaliah; Alpha Fadila Juliana Rahman; Dewi Puspitasari; Dwi Indah Rahayu (Journal of Innovation in Educational and Cultural Research, 2024)
The number of scientific publications published by countries reflects their ability to innovate. The government has made several efforts to encourage the State Civil Apparatus (ASN) to publish innovative scientific papers relevant to the ASN's functional scope of duties. One of these attempts is to provide basic scientific writing training. Basic scientific writing training is designed to accommodate participants from various backgrounds, including age, functional position, and functional position level. This research aims to determine whether cross-generational collaboration, cross-functional positions collaboration, and cross-level functional positions collaboration can produce a better quality of scientific writing content and seminars. This research involved 160 participants in 2023, divided into 80 coaching groups. Data were analyzed using descriptive statistics, boxplots, and cross-tabulation. The data was then analyzed further using ANOVA inferential statistics and Mann-Whitney non-parametric statistics. The results of data processing and analysis show that cross-generation collaboration and cross-level functional position can lead to significant improvements in scientific writing. On the other hand, cross-functional position collaboration delivers comparable results to coaching groups without collaboration. This study is expected to make a significant contribution to improving the quality of scientific papers written by participants with different functional positions, functional position levels, and generations.